Pembelajaran Bentuk-Bentuk Aljabar Berlandaskan pada Teori Situasi Didaktis pada Siswa Sekolah Menengah Atas di Yayasan Graha Asuh Jabal 165 Kabupaten Bandung - Nadya Syifa Utami; Aswin; Ade Riastuti; Woro Anglia Banda Sutomo; Khairunnisa; Nurdiyah Kurniati; Putri Armania; Al Jupri (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Algebra becomes an essential topic for all school mathematics topics. Nevertheless, many students still experience difficulties in learning algebra, one of them is senior high school students in Yayasan Graha Asuh Jabal 165, Kabupaten Bandung. Lack of effective learning activity in the class becomes the primary source for students’ difficulty. As an attempt to overcome this problem, the theory of didactic situation (TDS) could be adopted as a reference to implement the learning activity that possibly engages the students to be more active in the learning process. Therefore, this activity is held to help students in understanding the concept of algebraic forms with the learning based on the TDS. The method of this activity consisted of three stages, that was 1) the analysis of students’ difficulty in understanding the algebraic forms, 2) the learning implementation based on the TDS, and 3) the evaluation of students’ learning. The result shows that in the analysis stage, many students did not understand the concept of variables, coefficients, constants, equations, and algebraic operations. The next stage is learning implementation based on the TDS which comprises of the situation of action, formulation, validation, and institutionalization. The last one is evaluation where all students manage to understand the concept of algebraic forms and their application in daily life. This shows an improvement of their conceptual understanding in algebra.